Assessment of the implications of the CARP Law as a reform strategy - Legada, Ric Tan (Philippine Journal of Public Administration, 1989)
This paper argues that the Comprehensive Agrarian Reform Program (CARP) law contains some provisions that are contrary to the letter and spirit of the 1987 Constitution. It has provisions that tend to favor the multinational (or more accurately, transnational) corporations and corporate farms which were noteven mentioned in the Constitution as groups to be given preferential attention. On the other hand, there are sectors that are mentioned in the Constitution that were not given preferential attention in the CARP law particularly the cultural communities. The Torrens system which is contrary to the customs and traditions of some of the cultural communities was made to prevail over the rights of the tribal groups to their ancestral lands. Given this situation, there is a need to pass amendatory legislations to remove some of the defects of the 1988 CARP law.